Commentaires sur les dernières modifications apportées à la loi sur les assurances du Québec - Létourneau, Alain (Assurances, 1981)
A few months ago, Me Alain Létourneau has made an analysis of the changes brought recently to the Quebec Insurance Law. ln this review, he comments on the old and the new wording of the most important articles. ln our opinion, this is a very interesting study of the points which have been modified in order either to simplify or to clear the meaning of the insurance law.